Robust Gaussian-base radial kernel fuzzy clustering algorithm for image segmentation - Mújica-Vargas, Dante; Carvajal-Gámez, Blanca; Ochoa, Genaro; Rubio, José (Electronics letters, 2019)
To perform the image segmentation task, in this Letter, a kernel fuzzy C-means algorithm is introduced, strengthened by a robust Gaussian radial basis function kernel based on M-estimators. It is well-known that these kernels consider the squared difference as a similarity measure, which is not robust to atypical data. In this regard, the main motivation of this contribution is to improve the atypical information tolerance of these kernels, in order to make a better clustering of pixels. Experimental tests were developed considering colour images. The robustness and effectiveness of this proposal are verified by quantitative and qualitative results.